CX3CL1 release during immunogenic apoptosis is associated with enhanced anti-tumour immunity - Naessens, Faye; Demuynck, Robin; Vershinina, Olga; Efimova, Iuliia; Saviuk, Mariia; De Smet, Greet; Mishchenko, Tatiana A.; Vedunova, Maria V.; Krysko, Olga; Catanzaro, Elena; Krysko, Dmitri V. (Frontiers in Immunology, 2024)
Immunogenic cell death (ICD) has emerged as a novel option for cancer immunotherapy. The key determinants of ICD encompass antigenicity (the presence of antigens) and adjuvanticity, which involves the release of damage-associated molecular patterns (DAMPs) and various cytokines and chemokines. CX3CL1, also known as neurotactin or fractalkine, is a chemokine involved in cellular signalling and immune cell interactions. CX3CL1 has been denoted as a "find me" signal that stimulates chemotaxis of immune cells towards dying cells, facilitating efferocytosis and antigen presentation. However, in the context of ICD, it is uncertain whether CX3CL1 is an important mediator of the effects of ICD. In this study, we investigated the intricate role of CX3CL1 in immunogenic apoptosis induced by mitoxantrone (MTX) in cancer cells. The Luminex xMAP technology was used to quantify murine cytokines, chemokines and growth factors to identify pivotal regulatory cytokines released by murine fibrosarcoma MCA205 and melanoma B16-F10 cells undergoing ICD. Moreover, a murine tumour prophylactic vaccination model was employed to analyse the effect of CX3CL1 on the activation of an adaptive immune response against MCA205 cells undergoing ICD. Furthermore, thorough analysis of the TCGA-SKCM public dataset from 98 melanoma patients revealed the role of CX3CL1 and its receptor CX3CR1 in melanoma patients. Our findings demonstrate enhanced CX3CL1 release from apoptotic MCA205 and B16-F10 cells (regardless of the cell type) but not if they are undergoing ferroptosis or accidental necrosis. Moreover, the addition of recombinant CX3CL1 to non-immunogenic doses of MTX-treated, apoptotically dying cancer cells in the murine prophylactic tumour vaccination model induced a robust immunogenic response, effectively increasing the survival of the mice. Furthermore, analysis of melanoma patient data revealed enhanced survival rates in individuals exhibiting elevated levels of CD8+ T cells expressing CX3CR1. These data collectively underscore the importance of the release of CX3CL1 in eliciting an immunogenic response against dying cancer cells and suggest that CX3CL1 may serve as a key switch in conferring immunogenicity to apoptosis.